Managing trauma and disease of the incisors and canines. (2nd July 2020) - Barnett, Tim
Abstract : Equine incisors and canines are generally less affected by primary disease than the cheek teeth but are arguably more prone to external traumatic events and damage from bits and tack. The principles of investigating these teeth are the same as with the cheek teeth, and involve complete and thorough clinical examination usually with diagnostic imaging.